Dual‐Phase Engineering: Dual‐Phase Engineering of Nickel Boride‐Hydroxide Nanoparticles toward High‐Performance Water Oxidation Electrocatalysts (Adv. Funct. Mater. 38/2020). (17th September 2020) - Hong, Yu‐Rim; Kim, Kang Min; Ryu, Jeong Ho; Mhin, Sungwook; Kim, Jungin; Ali, Ghulam; Chung, Kyung Yoon; Kang, Sukhyun; Han, HyukSu
Abstract : In article number 2004330, HyukSu Han and co‐workers develop a novel material design concept of dual‐phase engineering via facile chemical etching towards a highly efficient and robust oxygen evolution reaction electrocatalyst. A high number of adsorption sites and facile charge transfer are simultaneously secured through the dual‐phase engineering concept.